The influence of technological factors on individualâs intention towards knowledge sharing practice - Ali, A.A. (Inderscience Enterprises Ltd., 2018)
Knowledge sharing has been receiving the highest concern among knowledge management processes. In fact, the practice of knowledge sharing in an organisation is influenced by employeesâ intention for sharing knowledge. This paper investigates the influence of knowledge sharing systems and Web 2.0 on the individualâs intention for knowledge sharing. Likewise, this paper examines the impact of knowledge sharing intention on the practice of knowledge sharing in organisations, particularly in oil and gas industry. Accordingly, a model was proposed, and research hypotheses were developed. Data were collected using a survey method. Measurements were verified through reliability analysis. Preliminary statistical analysis were completed. Then, structural equation modelling approach was used to evaluate the research model and test the hypotheses. The findings indicated that both knowledge sharing systems and Web 2.0 platform positively influence knowledge sharing intention. Besides, the intention to share knowledge has a positive influence on the knowledge sharing practice within organisations. Copyright Â© 2018 Inderscience Enterprises Ltd.